Analysis of Human Resource Development Training in Improving Employee Performance - Heribertus Gulo; Maria Magdalena Bate'e; Eliagus Telaumbanua; Heseziduhu Lase (Manunggal Halim Jaya, 2024)
In the contemporary period marked by globalization and modernization, Indonesian society has made significant strides, particularly in the fields of information and technology. Despite these advancements, there remain challenges that necessitate the development of individuals into exceptional human beings equipped with comprehensive skills. This study focuses on evaluating the effectiveness of human resource development training at the National Narcotics Agency office in Gunungsitoli City. The objective is to ascertain the implementation and impact of such training programs on employee performance. Employing a qualitative field research approach, the study was conducted at the aforementioned office, with agency employees serving as key informants. Data were primarily gathered through interviews, and the analysis utilized descriptive methods to articulate the current conditions observed in the field. Findings from the research indicate that training and development are crucial for enhancing employee competencies and aligning them with the organization’s vision and mission, thereby fostering an adept workforce at BNNK Gunungsitoli.